Knowledge, attitude, and practices in response to COVID-19 pandemic in Indian population - Vyas, Himali; Goyal, Raunak; Meena, Jitendra Kumar; Mathur, Medha; Yadav, Arvind (International Journal of Research in Medical Sciences, 2020)
Background: The World Health Organization (WHO) had reported COVID-19 disease as a pandemic in March 2020, following which India witnessed more than 29,451 cases on 29th April. Correct knowledge about the disease, the right attitude, and response to infection control recommendations among people is of utmost importance to limit the contagion. Methods: A Cross-Sectional, web-based online study was conducted for five days. The responses (N= 1231) were collected across social networks using snowball sampling. The survey questionnaire assessed the knowledge, attitude, and practical aspects of participants for COVID-19. Knowledge items assessed the causative agent of COVID-19, it’s clinical symptoms, routes of transmission, preventive measures etc. Positive or negative attitudes towards mask usage and restriction compliance were assessed. Socio-demographic data and scores were de-identified and analyzed using appropriate statistical tests. Results: The mean age of participants (N=1231) was 32.3±13.7 years and 60.9% were males. High knowledge years and 60.9% participants were males. High knowledge accuracy rate of 84.5% and a mean score of 10.19±1.6 out of 12 was observed. Mean attitude and practice scores were 2.33±0.66 (3) and 1.97±0.16 (2) respectively. A significantly higher knowledge status was observed among females, medical workers, students, and homemakers. Similarly, better attitudes were noticed in males, adults (30-60 years), graduates, and those in job/service. As for practices, no such difference was noticed as more than 98% of participants were compliant to lockdown restrictions and practiced proper distancing and personal hygiene measures. Conclusions: Satisfactory awareness and response were observed owing to the public awareness campaign. Knowledge gaps, poor attitudes, and prevailing myths need to be addressed through targeted communication strategy.